Comparison and improvement in primary airway fibroblast culture across different mammalian species - Hong, L; Song, D; Zeng, Y (Cellular and molecular biology (Noisy-le-Grand, France), 2015)
This study aims to establish rabbit, rat and human models of primary airway fibroblasts, improve existing culture methods of human, and provide alternatives to benign airway stenosis in vitro. We used conventional «tissue adherent method» to culture airway primary fibroblasts extracted from New Zealand rabbits, Sprague-Dawley (SD) rats and human subjects. To improve quality of this culture, we combined the «tissue adherent method» with « trypsinization", and compared the success rate of the two approaches. Cultures were examined using an inverted microscope, following hematoxylin-eosin and immunohistochemical staining. The different species were identified based on the total number of chromosomes. We successfully cultured primary airway fibroblasts isolated from three species. Human airway primary fibroblasts are more difficult to culture. The efficiency of culture is low, when using the «tissue adherent method». However, the rate of successful culture is improved when combined with the "trypsinization", and by using the «serum adherent, organizing tablet» technology. In conclusion, we demonstrate that primary airway fibroblasts from three mammalian species can be cultured successfully in vitro, for a reliable cellular model of benign airway stenosis. Culturing human primary airway fibroblasts is technically more challenging than the other two species. It is necessary to improve it.